2019
DOI: 10.1093/abm/kaz019
|View full text |Cite
|
Sign up to set email alerts
|

Moving in Sync: Hourly Physical Activity and Sedentary Behavior are Synchronized in Couples

Abstract: Background Overall time spent in moderate-to-vigorous intensity physical activity (MVPA) and sedentary behavior are both correlated in couples. Knowledge about the nature and psychosocial correlates of such dyadic covariation could inform important avenues for physical activity promotion. Purpose The present study investigates hour-by-hour covariation between partners (i.e., synchrony) in MVPA and sedentary behavior as partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 55 publications
3
43
0
1
Order By: Relevance
“…Close relationships are likely to have an impact on adults' levels of PA. 20 Therefore, the aim of our study was to objectively assess habitual PA and SB in couples consisting of end-stage (pre-arthroplasty) OA patients and their spouses as well as in control couples. In addition to the individual levels of performance, which largely depend on age and BMI, 48 we focused on the deviance between the spouses (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Close relationships are likely to have an impact on adults' levels of PA. 20 Therefore, the aim of our study was to objectively assess habitual PA and SB in couples consisting of end-stage (pre-arthroplasty) OA patients and their spouses as well as in control couples. In addition to the individual levels of performance, which largely depend on age and BMI, 48 we focused on the deviance between the spouses (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Most scientific research on PA focuses only on the individual and ignores the social environment, although it is already known that close relatives strongly influence this behavior. [18][19][20] Social learning theory suggests that people who spend a lot of time together emulate each other's behavior. 21 Especially among spouses, strong evidence has been found for the concordance of health behaviors that extends into later life.…”
Section: Synchronized Behavior In Couplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated daily life assessments allow for granular assessment of couples as they engage in their connected daily life routines (Bolger & Laurenceau, 2013). Using this approach, we recently showed that physical activity and sedentary time is strongly linked between older spouses (Pauly et al, 2020). To our knowledge, there is only one published study to date (Harada, Masumoto, & Kondo, 2018) that investigated sedentary behavior in older couples, and they did not use repeated daily life assessments.…”
Section: Introductionmentioning
confidence: 99%